RESEARCH DESIGNS AND THEORETICAL FRAMEWORKS OF GAMIFICATION IN EDUCATIONAL CONTEXT: A SYSTEMATIC LITERATURE REVIEW - Agus Rahmat; Iskandar Iskandar; Amirullah Amirullah; Dias Wahyu Rawikarani (Al-Irsyad: Journal of Education Science, 2026)
This systematic literature review looks at how gamification strategies are being used in education that focuses on the trends in research designs and the theories used in educational gamification studies, given the limited synthesis regarding these two aspects. The analysis covers 16 research articles published from 2020 to 2025. Information was gathered from Google Scholar and ERIC by using specific rules to decide either data inclusion or exclusion, and then it was examined through a process called thematic synthesis. The results show that most research on gamification uses quantitative and quasi-experimental designs, while mixed-methods and qualitative approaches are used less often. Additionally, the review shows that several studies use gamification but don't clearly base their methods on recognized learning or motivation theories. However, some studies do mention Self-Determination Theory and ideas related to active learning. Overall, the synthesized evidence indicates that gamification enhances motivation, engagement, and learning outcomes. However, future studies should use more theory-based approaches and different methods to make their findings more reliable and relevant to teaching.